INSTITUTIONAL IMPROVEMENT OF AN INDONESIAN ISLAMIC HIGHER EDUCATION - Chusnul Chotimah (IAIN Tulungagung, 2019)
Scholarly discussions on institutional development could be divided into two categories; “Blue Ocean Strategy” and “Red Zone Strategy” approaches. Blue Ocean Strategy characterized by creating new innovation and market without locating institution to compete with other institution. Meanwhile, Red Zone Strategy emphasizes on initiating a different innovation in order to contest in the marketplace. This article examines the transformation of IAIN Tulungagung from STAIN to IAIN in 2013. This article employs qualitative approach and demonstrates that IAIN Tulungagung has created a creative innovation such as initiating Edu-fair event to attract new students, bulding a new brand, establishing the advance program to promote its institution, and developing the human capital. This strategy indicates that IAIN Tulungagung applies Blue Ocean Strategy in developing its institution such as Decrease-Delete-Create-Increase becomes Passive-Save-Create-Increase.